2014
DOI: 10.1016/j.jep.2013.10.063
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, antimicrobial and toxicological properties of Schinus molle L. essential oils

Abstract: a b s t r a c tEthnopharmacological relevance: Schinus molle L. has been used in folk medicine as antibacterial, antiviral, topical antiseptic, antifungal, antioxidant, anti-inflammatory, anti-tumoural as well as antispasmodic and analgesic; however, there are few studies of pharmacological and toxicological properties of Schinus molle essential oils. The aim of this study was to evaluate the antioxidant and antimicrobial activities of Schinus molle leaf and fruit essential oils, correlated with their chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
105
3
18

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(137 citation statements)
references
References 43 publications
11
105
3
18
Order By: Relevance
“…Components of the essential oil and the oleoresin of S. terebinthifolius are not the same, which was expected as the extraction methods used can lead to different kind of extracts. Both results are in agreement with MARTINS et al (2014).…”
Section: Gc-ms Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…Components of the essential oil and the oleoresin of S. terebinthifolius are not the same, which was expected as the extraction methods used can lead to different kind of extracts. Both results are in agreement with MARTINS et al (2014).…”
Section: Gc-ms Analysissupporting
confidence: 91%
“…SOUTO et al (2012) reported the insecticidal activity of the essential oil of Piper aduncum, Piper marginatum, Piper divaricatum and Piper callosum against the ant Solenopsis saevissima and detected various compounds by Gas Chromatography coupled with Mass Spectrometry (GC-MS) that were previously known as having insecticidal activity. MARTINS et al (2014), studied the essential oil of Schinus molle essential oils (the leaf and the fruits) and reported that both oils have low antioxidant activity, antimicrobial activity against Gram + and Gram -bacteria and spoilage fungi with low toxicity in vivo in mice (2000mg kg -1 ). KAPOOR et al (2009) demonstrated the antioxidant and scavenging activity of Piper nigurm essential oil and oleoresins, which have important applications in food chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that S. areira essential oils isolated from leaves and fruits have antibacterial activity (Celaya, Alabrudzinska, Molina, Viturro, & Moreno, 2014). Essential oils of a related specie, Schinus molle, also exhibited antioxidant and antimicrobial properties (Martins et al, 2014). In this study, we optimized the extraction of nonvolatile antioxidant compounds from S. areira leaves by ultrasound-assisted extraction, in order to determine the potential of these plants as sources of natural antioxidants.…”
Section: Introductionmentioning
confidence: 99%
“…It provides cellular protection against oxidative stresses that is induced by the fine suspended dust particles by controlling antioxidant enzyme activity. It is also shown to be associated with a modulation of epigenetic biomarkers that are linked to a stronger skin barrier and reduces skin permeability that is induced by environmental stress and increased skin hydration [40].…”
Section: Use Of Anti-oxidantsmentioning
confidence: 99%